2015
DOI: 10.1007/s00426-015-0698-1
|View full text |Cite
|
Sign up to set email alerts
|

Body ownership and response to threat

Abstract: A virtual-reality setup was used to investigate the relationship between perceived body ownership and subjective anxiety, as assessed by an anxiety inventory (SA-I). A pilot study confirmed that synchrony between the participant’s real hand movements and the movements of a virtual effector induced perceived ownership illusions. The illusions were comparable for virtual human hands and virtual cat claws, even though the overall acceptance was greater for human hands. In Experiment 1, participants used the virtu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 27 publications
2
34
0
Order By: Relevance
“…With the recent technological developments, avatars are now highly used in VR for research purposes, e.g., for 3D graphics and games research [43], behavioral research in psycholinguistic [11], or psychological research in general [47]. Indeed, avatars can be altered in numerous ways to assess changes in users' behaviors.…”
Section: Related Work 21 Embodiment In Vrmentioning
confidence: 99%
See 1 more Smart Citation
“…With the recent technological developments, avatars are now highly used in VR for research purposes, e.g., for 3D graphics and games research [43], behavioral research in psycholinguistic [11], or psychological research in general [47]. Indeed, avatars can be altered in numerous ways to assess changes in users' behaviors.…”
Section: Related Work 21 Embodiment In Vrmentioning
confidence: 99%
“…One more competitive, where users had to compete for the same moles, and another less competitive, where they only focused on their moles. Finally, the addition of potentially harmful elements in VEs is commonly used in embodiment studies to assess behavioral responses [12,47]. Thus, we considered the additional independent variable (Danger) whether there was a potential threat to the virtual avatar (Danger) or not (Safe).…”
Section: Experimental Designmentioning
confidence: 99%
“…In these studies, the evidence shows that subjects feel that they have swapped bodies with another person (Petkova and Ehrsson, 2008), a plastic mannequin (Petkova and Ehrsson, 2008), a Barbie doll (Van der Hoort et al, 2011), a digital avatar (Maselli and Slater, 2013), an invisible body (Guterstam et al, 2015), and even a body located in the front of them (Lenggenhager et al, 2007). These multisensory stimuli elicit a blurriness in the identity perception of self and other (Paladino et al, 2010) and may even drive participants to present a subjective anxiety to threats targeted at their virtual hand (Zhang and Hommel, 2016). Body Ownership, or the sense of embodiment, is comprised of the sense of self-location, the sense of agency and the sense of body ownership (Kilteni et al, 2012).…”
Section: Perceptual Illusions In Vr Presence [Place Illusion (Pi) Andmentioning
confidence: 99%
“…Interestingly, the results of experiment 1 also showed the effects of agency and ownership on perceived anxiety were different, which suggested that the informational bases for these two judgments do not entirely overlap, showing a discrepancy between ownership and agency (Kalckert & Ehrsson, 2012;Kalckert & Ehrsson, 2014). Also, previous studies showed that people experience more anxiety in the face of threat targeting a virtual effector that they also perceive more ownership for (Ma & Hommel, 2015;Zhang & Hommel, 2016); in order to know more about how positive and negative events can interact with sense of agency and sense of ownership in terms of anxiety, we performed experiment 2 which was very similar with experiment 1 except each participant was assigned to only one kind of task, catching coins or avoiding knives.…”
Section: Resultsmentioning
confidence: 87%
“…We systematically found increased anxiety scores in conditions with synchronous relationships between virtual images and real hands. As these conditions also increase the perception of sense of ownership, it makes sense to assume that bottom-up information (provided through synchrony) and top-down information (provided by modality) are integrated into a coherent percept (Zhang & Hommel, 2016). The sense of agency and sense of ownership as two major components of minimal self existing in the process of self-other recognition affect the higher level emotional experience via bodily self-perception (Zhang & Li, 2016).…”
Section: Resultsmentioning
confidence: 99%